2020
DOI: 10.3390/bioengineering8010001
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Cell Cultures on Electrospun Poly(ε-Caprolactone) as a Potential Tool for Preclinical Studies on Anticancer Treatments

Abstract: During anticancer drug development, most compounds selected by in vitro screening are ineffective in in vivo studies and clinical trials due to the unreliability of two-dimensional (2D) in vitro cultures that are unable to mimic the cancer microenvironment. Herein, HCC1954 cell cultures on electrospun polycaprolactone (PCL) were characterized by morphological analysis, cell viability assays, histochemical staining, immunofluorescence, and RT-PCR. Our data showed that electrospun PCL allows the in vitro formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Compared to the 2D culture, a decrease in drug sensitivity to doxorubicin and electroporation/bleomycin was also observed in the 3D scaffold model. The possible reason for a reduction in sensitivity might be the abundant CSC population or ECM presence ( 62 ). The synthetic polymers, PCL and PLA, were capable of mimicking the structural properties of native ECM, but they failed in providing the biochemical signals needed for cell-ECM communication.…”
Section: Fibrous Scaffolds As In Vitro Cancer Modelsmentioning
confidence: 99%
“…Compared to the 2D culture, a decrease in drug sensitivity to doxorubicin and electroporation/bleomycin was also observed in the 3D scaffold model. The possible reason for a reduction in sensitivity might be the abundant CSC population or ECM presence ( 62 ). The synthetic polymers, PCL and PLA, were capable of mimicking the structural properties of native ECM, but they failed in providing the biochemical signals needed for cell-ECM communication.…”
Section: Fibrous Scaffolds As In Vitro Cancer Modelsmentioning
confidence: 99%
“…Several studies have demonstrated the efficacy of hydrophobic materials such as ethyl cellulose, polycaprolactone (PCL), poly (lactic-co-glycolic acid), and polylactic acid in sustaining drug release ( Sánchez-Romate et al, 2020 ; Ahmadi et al, 2022 ; Wang S. et al, 2022 ; Dodda et al, 2022 ; Lee et al, 2022 ; Vlachopoulos et al, 2022 ). PCL, a hydrophobic material processing good biocompatibility, is extensively involved in the preparation of biomedical materials ( Jiménez-Suárez et al, 2020 ; Bazzolo et al, 2021 ; Sánchez-Romate et al, 2021 ; Baghali et al, 2022 ; Setia Budi et al, 2022 ; Shahverdi et al, 2022 ). In the treatment of osteoporosis, simvastatin (SIM) has been exploited for inducing bone regeneration ( Castro et al, 2018 ; Rezk et al, 2020 ; Karanikola et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Designing and developing pro-angiogenic electrospun PCL nanofibers and evaluating their usefulness in various tissue engineering and regenerative medicine settings is an active field of research [ 24 ]. Bazzolo et al [ 25 ] conducted breast cancer cell cultures on electrospun PCL as a potential tool for preclinical studies on anticancer treatments. Various electrospun nanofibers made of natural and synthetic polymers are often used to incorporate biomolecules and peptides to improve the physico-chemical/mechanical and biological properties of PCL fibers.…”
Section: Introductionmentioning
confidence: 99%
“…The study by Dettin M et al [ 27 ] investigates the influence of increasing concentrations self-assembling peptides (SAP) with PCL on the physico-chemical, mechanical and biological properties of PCL fibers. The study found that, as compared with bare PCL, SAP enrichment increased the number of metabolic active h-osteoblast cells, fostered the expression of specific osteoblast-related mRNA transcripts, and guided calcium deposition, revealing the potential application of PCL-SAP scaffolds for the maintenance of osteoblast phenotype [ 25 ].…”
Section: Introductionmentioning
confidence: 99%